Answer:
The statement which shows a sum rewritten in the form a ( b + c ) such that the integers b and c have no common factor is:
A. 25 + 15 = 5 ( 5 + 3 )
D. 99 + 66 = 33 ( 3 + 2 )
E. 23 + 69 = 23 ( 1 + 3 )
Explanation:
A.
25 + 15 = 5 ( 5 + 3 )
This is the correct form.
Because greatest common factor of 5 an 3 is: 1
Hence, 5 and 3 have no common factor.
Also,
5 ( 5 + 3 )= 5×5+5×3
i.e.
5 ( 5 + 3 )= 25+15
Hence, option: A is correct.
B.
12 + 16 = 9 ( 3 + 7 )
This property is wrong because.
9 ( 3 + 7 )=9×3+9×7
i.e.
9(3+7)=27+63
Hence, option: B is incorrect.
C.
63 + 42 = 7 ( 9 + 6 )
The expression is correct.
but,
9 and 6 have a common factor as: 3
Hence, option: C is incorrect.
D.
99 + 66 = 33 ( 3 + 2 )
This expression is also correct.
Since,
33(3+2)=33×3+33×2
i.e.
33(3+2)=99+66
Also, 3 an 2 do not have a common factor.
Hence, option: D is correct.
E.
23 + 69 = 23 ( 1 + 3 )
The expression is correct.
since,
23 (1+3)=23×1+23×3
i.e.
23 (1+3)=23+69
Also, 1 and 3 do not have a common factor.
Hence, option: E is correct.